Perilaku Proaktif Siswa dalam Belajar di SMA - Setia Nur Fatimah; Afrizal Sano (Universitas Negeri Padang, 2021)
Proactive behavior is a concrete reflection of one's actions. This research is motivated by the existence of students who do not have proactive behavior in learning. This study aims to describe the proactive behavior of students in terms of freedom in choosing responses, ability to take initiative, and ability to take responsibility for students in learning at SMA Adabiah 2 Padang. This type of research is descriptive. The study population was 665 people with a sample of 203 students who were drawn using the Stratified Random Sampling technique. The instrument used was a questionnaire. The data analysis technique is the percentage. The results showed that the proactive behavior of students in learning in terms of: (1) freedom in choosing responses was high, (2) ability to take initiative was high, and (3) ability to take responsibility was also high.